Surgical site infections in ear surgery: Hair removal effect; A preliminary, randomized trial study - Kattipattanapong W. (2014)
Objective. (1) To compare the rate of surgical site infections in ear surgery between groups with and without hair removal and (2) to study factors associated with surgical site infections. Study Design. A preliminary, randomized, controlled trial. Setting. University hospital. Subjects and Methods. The study was conducted in a group of 136 patients who underwent surgery for external or middle ear disease via the post-auricular approach at Chiang Mai University Hospital from May 2010 to May 2011. Demographic data, surgical site infection within 30 days postoperatively, and associated factors were recorded. Results. Fifty-eight cases were men and 78 cases women. Demographic data between the 2 groups were compared. Age, gender, the side of operated ear, types of anesthesia, emergency or elective setting, body mass index, history of alcohol and/or tobacco use, underlying diseases, operative time, and the length of hospital stay revealed no significant differences. A postoperative surgical site infection developed in 5 patients: 3 in the group with hair removal (4.5%) and 2 in the group without hair removal (2.8%) (P value = 0.674, Fisher's exact test). All infected cases had undergone mastoidectomy. Conclusions. Surgical site infection rates between the 2 groups (with and without hair removal) demonstrated no difference. Hair removal prior to ear surgery via post-auricular incision had no effect on the rate of surgical site infection. © American Academy of Otolaryngology - Head and Neck Surgery Foundation 2012.